La prise en charge et modalités thérapeutiques de La menace d’accouchement prématuré - MOSBAH Fatima Zohra; MOUILHI Meriem; Encadreur : Dr. HAMBLI (Université Amar Telidji de Laghouat Faculté de Médecine, 2022)
The main objective of our study is to identify and to evaluate the therapeutic modalities of the threat of premature delivery at the level of the EHS Elhakim Saadan of Laghouat. The secondary objectives are: To determine the frequency, to study the socio-epidemiological aspects and the clinical and paraclinical profile of patients and to analyze the different risk factors and the etiologies of MAP. Materiel and method: The study was descriptive retrospective covering a period of 12 months, which runs from 01 January 2020 to 31 December 2020; this study was carried out at the level of EHS Elhakim Saadan of Laghouat. Results: During the study period, 154 cases were hospitalized at the GHR unit for a MAP out of a total of 2,057, or a frequency of )7.48%(. The average age was 27 years with extremes of 19 and 45 years. Risk factors are dominated by antecedent obstetricc : Spontaneous abortions (25.32%), premature delivery (7.14%) and Caesarean section (20.13%). The most common etiologies in our population are urinary tract infections (9.1%), genital infections (6.49%) and multiple pregnancy (3.25%). Almost half of the patients did not follow their pregnancy regularly, or (48.05%). Calcium inhibitors appear to be a simpler tocolytic to use than the oxytocin antagonist, (81.17%) of patients were treated with calcium inhibitors and (14.93%) with oxytocin antagonists, none with beta-mimetic. (65%) of patients treated with Atosiban gave birth after 37 SA, but (54%) who were already treated with calcium channel blockers gave birth at term. The lower route was the most common mode of delivery (73%). Conclusion: The choice of the first line of tocolysis in terms of safety, efficiency and cost is a subject of controversy; it depends on general criteriar such as counter-indications or drug tolerances and criteria specific to each institution such as the availability and cost of the molecule. Regular and quality prenatal consultation should be done for all pregnant women in order to determine risk factors and to detect signs in favour of a MAP for adequate management in order to reduce the rate of premature delivery that has serious consequences.
96 p.